MEKANISME PENGEMBALIAN ASET NEGARA HASIL TINDAK PIDANA KORUPSI - Bahri, Muhammad Syamsul; Marwiyah, Siti; Prawesthi, Wahyu; Amiq, Bachrul (Universitas Muhammadiyah Ponorogo, 2024)
Corruption is a despicable act that occurs every year. Corruption is classified as a heinous act and has a major impact on state finances, causing harm to many parties. Investigation, prosecution and court hearings in corruption cases must take priority over other cases in order to resolve them as quickly as possible. The aim of this research is to understand and analyze law enforcement for criminal acts of corruption in Indonesia and to understand and analyze the mechanism for returning state assets resulting from criminal acts of corruption. The method used in this research is a normative research method. It is a legal research which places the law as a building system of norms. Law Number 20 of 2001 concerning Corruption Crimes regulates mechanisms or procedures that can be used to return assets through criminal and civil channels. The mechanism for returning state assets resulting from criminal acts of corruption can be carried out using two mechanisms, which is criminal route as regulated in UNCAC and the civil route (civil forfeiture). The criminal route is intended to provide a deterrent effect to corruptors so that they do not repeat criminal acts of corruption. Civil forfeiture is intended to return state assets resulting from criminal acts of corruption with evidence obtained from the criminal process, namely tracing and freezing assets. The key to success lies with each country, so it cannot be determined which mechanism is the best. Elements of success in efforts to return assets resulting from criminal acts of corruption must take into account several factors, one of which is the perspective that the law enforcement approach in Indonesia still focuses on punishing perpetrators (in personam), not confiscating assets resulting from crime.